Pengembangan Strategi Pemasaran Pada Produk Makaroni Goreng (Cinlok) - Ayu Azizah; Faruq Lamusa; Harnida Waahyuni (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Entrepreneurship is said to be very important because it can increase economic growth in general in a country. The role of entrepreneurship in economic development includes more than just increasing output and income per capita, it also includes initiatives and determination of changes in the structure of business and society (Hisriich et al., 2008. CINLOK is a snack made from bantet macaroni, which is in the form of such as small bent pipes which are then fried and seasoned with various flavors such as balado, sweet and spicy balado, roasted corn, sweet corn, cheese, spicy lime leaves, and extra hot CINLOK was founded on October 30 2020, but had was halted due to the Covid-19 outbreak and restarted while participating in the independent entrepreneurial MBKM program on August 29 2022. marketing strategy is of course mandatory for a business to increase sales.CINLOK has several marketing strategies developed in order to attract consumers and increase sales.